Critical analysis of IAS 2 „Stocks”, version of 2005 - UNTARU, Mircea (Annals of Spiru Haret University. Economic Series, 2016)
This research paper aims to achieving a comparative analysis of the two versions of IAS 2 „Stocks” (variants of 1993 and 2005). The research is part of a larger study regarding the accounting processes carried out for the acknowledgement and assessment of the company stock, and the purpose of the study is to develop a new framework methodology for the acknowledgement and assessment of stocks. The research is based on a series of work hypotheses: (I1) IAS 2 variant of 1993 needs to be reviewed according to the regulations and normatives in force; (I2) the necessity to review IAS variant of 1993 derives from the critics raised by the regulating authorities for stock and shares, by the professional accountants and by other interested parties, with regard to the reduction or elimination of alternatives, redundancies and conflicts from standards, and the solving of convergence issues; (I3) the 2005 variant of IAS 2 is the result of a limited reviewing of the 1993 variant of IAS 2, and needs to be further modified.